2019
DOI: 10.1002/fsn3.986
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of engineering properties for waste control of tomato during harvesting and postharvesting

Abstract: In Iran, more than 30% of agricultural products turn into waste at different stages from harvesting to consumption. Thus, main factors for performing of this present study are including of: (a) the importance of tomato as an agricultural product and (b) lack of information about reducing waste during tomato processing. In this study, some physical, nutritional, mechanical, and hydrodynamic properties of tomato were measured under standard conditions. Physical properties included the length, width, thickness, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Then, pistachio kernels were taken out of their skin without any breaks. To determine the initial MC of the pistachios, 20 g samples was then placed in an oven (Memmert UNE 500 model) with a temperature of 105 ± 1°C for 24 hr and dried there (Jahanbakhshi, Rasooli Sharabiani, Heidarbeigi, Kaveh, & Taghinezhad, 2019a). The samples were weighed using a digital scale (USA, GF600 model with a precision of 0.01 g) before and after being placed in the oven.…”
Section: Methodsmentioning
confidence: 99%
“…Then, pistachio kernels were taken out of their skin without any breaks. To determine the initial MC of the pistachios, 20 g samples was then placed in an oven (Memmert UNE 500 model) with a temperature of 105 ± 1°C for 24 hr and dried there (Jahanbakhshi, Rasooli Sharabiani, Heidarbeigi, Kaveh, & Taghinezhad, 2019a). The samples were weighed using a digital scale (USA, GF600 model with a precision of 0.01 g) before and after being placed in the oven.…”
Section: Methodsmentioning
confidence: 99%
“…The growing world's population is constantly in need of food production, and agriculture plays a key role in this production (Eliaspour, Seyed Sharifi, & Shirkhani, 2020; Jahanbakhshi & Salehi, 2019; Jahanbakhshi, Abbaspour‐Gilandeh, & Gundoshmian, 2018; Jahanbakhshi, Yeganeh, & Shahgoli, 2019c; Momeny, Jahanbakhshi, Jafarnezhad, & Zhang, 2020). Maize is considered as one of the most important crops with a variety of uses such as the human and animal food, fodder, and industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the data obtained about the hydrodynamic properties of cantaloupe can be used in the transfer, separation, and sorting through water in order to reduce processing costs and product waste. In similar studies, researchers reported that parameters such as the buoyance force and drag force can be used in modeling terminal velocity and the time length for the fruit to move up or down in the fluid (Dadashi et al, ; Jahanbakhshi et al, ; Moradi et al, ; Tarighi, Mohtasebi, Heydari, & Abasghazvini, ).…”
Section: Resultsmentioning
confidence: 99%
“…So, by putting a sui separator in place, fruits can be sorted. Terminal velocity of fruits plays an important role in designing transfer equipment and different types of product cleaning systems (Jahanbakhshi, Rasooli Sharabiani, Heidarbeigi, Kaveh, & Taghinezhad, ; Kheiralipour et al, ). Some studies on this topic have measured terminal velocities for pomegranate (Dadashi et al, ), apple (Kheiralipour et al, ), apricot (Mirzaee et al, ) and tomato (Garavand, Rafiee, Keyhani, & Mirzaee, ).…”
Section: Introductionmentioning
confidence: 99%